PENERAPAN METODE IMPORTANCE PERFORMANCE ANALYSIS UNTUK MENGETAHUI TINGKAT KEPUASAN PENGUNJUNG PANTAI GANDORIAH PARIAMAN - Fajri, Rayhan Al (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Gandoriah Beach is one of the beaches located in Pasir Village, Central Pariaman District, Pariaman City. The combination of a strategic position, beautiful sea panorama and sloping contours, makes this beach one of the most popular beach attractions. This tourist area has tourism potential to be developed further, because the beach conditions are very attractive and beautiful. However, there are many weaknesses of Gandoriah Beach Tourism Area that are often complained about by visitors. Starting from the unclear SOP to the lack of public facilities that can support the needs of visitors. This study aims to determine the level of satisfaction of Gandoriah Beach tourism visitors and analyse the attributes that are considered important so that they can be used as material for improvement in increasing visitor satisfaction. This research uses descriptive method and quantitative approach with sample selection technique using accidental sampling and data analysis method with Importance Performance Analysis (IPA). The results showed that visitor satisfaction with Gandoriah Beach tourist attraction is still low so that some improvements to the attributes are needed to increase visitor satisfaction. The novelty of this research itself is that it is the first research to measure the level of visitor satisfaction at Gandoriah Beach using the Importance Performance Analysis (IPA) method